An experimental study on fatigue debonding growth of RC beams strengthened with prestressed CFRP plates. (15th December 2022) - Min, Xinzhe; Zhang, Jiwen; Li, Xing; Wang, Chao; Tu, Yongming; Sas, Gabriel; Elfgren, Lennart
Highlights: CFRP plate debonding was observed in both static and fatigue tests but with different modes of propagation. Fatigue damage accumulated in steel reinforcement during cyclical loading initiated CFRP plate debonding even when the CFRP plate strain was initially below the fatigue debonding strain threshold. Accumulated fatigue damage in the steel reinforcement is coupled to fatigue debonding growth of the CFRP plate via stress redistribution and thus affects the fatigue life of strengthened beams. Abstract: Externally bonded Fiber Reinforced Polymer (FRP) laminates are increasingly used to strengthen Reinforced Concrete (RC) members. However, FRP debonding remains a major drawback of this strengthening method. To better understand the mechanisms of FRP debonding, six RC beams strengthened with prestressed or non-prestressed Carbon Fiber Reinforced Polymer (CFRP) plates were subjected to static and fatigue loading. CFRP plate debonding was observed in both cases. However, the mechanism of debonding differed: under cyclical fatigue loading, debonding was initiated under both loading points simultaneously and propagated synchronously towards the nearest support whereas in static tests debonding began under a single loading point and progressed suddenly towards its adjacent support. The results also showed that stress redistribution induced coupling between accumulated fatigue damage in the steel reinforcement and fatigue debonding of the CFRP plate, accelerating the fatigue failure of the specimens.